High-temperature-resistant UV highlight plate and preparation process thereof
By adding moisture-proof solvent to the MDF substrate of UV highlighter plate and adopting a multi-layer coating process, nanotitanium dioxide, organosilicon compounds and silane coupling agents, the problems of deformation and coating peeling in high temperature environments are solved, and better high temperature resistance is achieved.
Patent Information
- Application Number
- CN202411697086.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
Traditional UV highlighter plates are prone to deformation or surface coatings fall off in high temperature environments, limiting their application range.
MDF containing moisture-proof solvent is used as the substrate and through a multi-layer coating process, including a sealing primer, a modified epoxy resin primer, an intermediate coating and a topcoat, which contains nanotitanium dioxide, an organosilicon compound and a silane coupling agent.
It improves the moisture-proof and mechanical properties of the material, reduces moisture intrusion, maintains the structural stability and performance of the material, reduces cracks and stratification caused by thermal stress in high-temperature environments, thereby improving high-temperature resistance.
Smart Images

Figure CN119505561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of UV high-gloss boards, in particular to a high-temperature resistant UV high-gloss board and a preparation process thereof. Background Art
[0002] UV high gloss board is a board whose surface is protected by UV light curing paint. Although traditional UV high gloss board has excellent gloss and good chemical stability, it is easy to deform or the surface coating layer will fall off under high temperature environment, which limits its application range. Therefore, it is an urgent need for the industry to develop a UV high gloss board that not only maintains the original advantages but also has good high temperature resistance. Summary of the invention
[0003] The purpose of the present invention is to provide a high-temperature resistant UV high-gloss board and its preparation process. By adopting MDF containing a moisture-proof solvent as a substrate to enhance the moisture-proof performance, by improving the moisture-proofness of the material, the intrusion of moisture can be reduced, thereby maintaining the structural stability and performance of the material in a high-temperature environment. The improved interface bonding can reduce cracks and delamination caused by thermal stress, thereby improving the high-temperature resistance of the material, and solving the problems raised in the above-mentioned background technology.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A high-temperature resistant UV high-gloss board comprises an MDF substrate, wherein the MDF substrate contains a moisture-proof solvent, and the surface of the MDF substrate is coated with a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating in sequence, wherein the intermediate coating contains nano titanium dioxide, an organic silicon compound and a silane coupling agent.
[0006] Preferably, the MDF substrate is made of the following materials: a wood fiber mixture, a synthetic resin and a moisture-proof solvent, the moisture-proof solvent includes paraffin emulsion, a silane coupling agent and polyvinyl alcohol, and the paraffin emulsion, the silane coupling agent and the polyvinyl alcohol are mixed in a ratio of 15:3:5.
[0007] Preferably, the concentration of the paraffin emulsion is 10%-20%, the concentration of the silane coupling agent is 2%-5%, and the concentration of the polyvinyl alcohol is 3%-7%.
[0008] Preferably, the preparation method of the synthetic resin is as follows: dissolving a urea-formaldehyde resin with low formaldehyde release in an appropriate amount of water to prepare a resin solution, adding urea to the resin solution, stirring evenly, and preparing a mixed resin. Urea can react with formaldehyde in the urea-formaldehyde resin to generate stable hexamethylenetetramine, thereby reducing formaldehyde release.
[0009] Preferably, the preparation method of the wood fiber mixture is as follows: select wood fibers of uniform size and length, remove impurities and dust in the wood fibers, add activated carbon and bamboo charcoal to the cleaned wood fibers, the added amount of activated carbon and bamboo charcoal is 0%-2% of the weight of the wood fibers, and obtain a wood fiber mixture. Activated carbon and bamboo charcoal can adsorb and reduce the release of harmful gases such as formaldehyde. They have good adsorption properties, can effectively adsorb free formaldehyde, and improve the environmental performance of the MDF substrate.
[0010] Preferably, the materials of the sealing primer are proportioned as follows by mass: 65%-75% waterborne polyurethane resin, 3-6% silane coupling agent, 0.5%-1% polysiloxane defoamer, 0.5%-1% acrylate leveling agent, and the balance is deionized water. The spraying thickness of the sealing primer is 10-20 μm.
[0011] Preferably, the materials of the modified epoxy resin base coating are proportioned as follows by mass: 65%-70% epoxy resin, 25%-30% aromatic amine curing agent, 2%-5% alumina, 1%-2% 2-hydroxy-2-methylpropiophenone, 1%-2% silane coupling agent, 0.5%-1% acrylate leveling agent, 1%-2% rubber particles, and acetone: balance. By selecting a curing agent that can maintain stability at high temperatures, the heat resistance of the epoxy resin can be improved. The addition of alumina further improves the overall high temperature resistance of the modified epoxy resin base coating. The addition of rubber particles can improve the flexibility and impact resistance of the epoxy resin and prevent the coating from falling off.
[0012] Preferably, the materials of the intermediate coating are proportioned as follows by mass: 65%-70% phenolic resin, 8%-12% nano-titanium dioxide, 8%-12% organosilicon compound, 3%-6% silane coupling agent, 0.5%-1% acrylic leveling agent, and the balance of acetone.
[0013] Preferably, the materials of the top coating are proportioned as follows by mass: 80% UV curing resin, 5% 2-hydroxy-2-methylpropiophenone, 1%-2% leveling agent, 0.5%-1% defoaming agent, and the balance of diluent.
[0014] Another technical problem to be solved by the present invention is to provide a preparation process of a high temperature resistant UV high gloss board, comprising the following steps:
[0015] Step 1: The wood fiber mixture is mixed with the synthetic resin solution. During the process, a moisture-proof solvent solution is added to make the resin evenly adhere to the fiber surface. The mixed fibers are evenly laid in the molding mold for hot pressing. After cutting, the MDF substrate is made. The mixed fibers form a fiber layer of a certain thickness in the mold. The fiber layer is preliminarily compacted by a pre-pressing machine to give it a preliminary shape and density. The pre-pressed fiber layer is sent to a hot press and hot-pressed under high temperature and high pressure conditions. During the hot pressing process, the resin will melt and solidify, so that the fibers are tightly combined together to form a board with a certain density and strength. The hot-pressed board needs to be gradually cooled in a cooling device to prevent deformation of the board. The formed board is cut according to the required size, and the surface of the board is sanded to make it smooth.
[0016] Step 2: Use a spray gun to evenly spray the prepared sealing primer on the surface of the MDF substrate, control the spraying thickness to 10-20μm, put the substrate sprayed with the sealing primer into a drying room, control the temperature at 60-80℃, and dry it for 30-60 minutes to ensure that the primer is completely dry;
[0017] Step 3: Spray the prepared modified epoxy resin primer evenly on the surface of the closed primer, control the spraying thickness to 10-20 μm, put the substrate sprayed with the primer into the UV curing equipment, turn on the UV lamp, and irradiate for 30-60 seconds to ensure that the primer is completely cured to form a uniform modified epoxy resin primer;
[0018] Step 4: Spray the prepared intermediate coating evenly on the surface of the modified epoxy resin base coating with a spraying thickness of 20-30 μm, put the substrate sprayed with the intermediate coating into a drying room, control the temperature at 60-80 ° C, and dry for 30-60 minutes to ensure that the intermediate coating is completely dry;
[0019] Step 5: Spray the prepared topcoat liquid evenly on the surface of the intermediate coating with a spraying thickness of 10-20μm. Place the substrate sprayed with the topcoat liquid into the UV curing equipment, turn on the UV lamp, and irradiate for 30-60 seconds to ensure that the topcoat liquid is completely cured to form a uniform high-gloss coating.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention discloses a high-temperature-resistant UV high-gloss board and a preparation process thereof. MDF containing a moisture-proof solvent is used as a substrate, a paraffin emulsion forms a hydrophobic film to reduce moisture penetration, a silane coupling agent can improve the interface bonding between fiber and resin and improve moisture-proof performance, polyvinyl alcohol can enhance the bonding force between fibers and reduce moisture absorption, and when these additives are used simultaneously, they can complement each other and jointly improve the moisture-proof performance and mechanical properties of the MDF substrate. A layer of water-based polyurethane sealing primer is coated on the surface of the MDF substrate to enhance moisture-proof performance. By improving the moisture-proof performance of the material, the intrusion of moisture can be reduced, thereby maintaining the structural stability and performance of the material in a high-temperature environment, and the improved interface bonding can reduce cracks and delamination caused by thermal stress, thereby improving the high-temperature resistance of the material, and nano-titanium dioxide and organic silicon compounds are added as high-temperature-resistant additives, and a silane coupling agent is added as a tackifier to improve the heat resistance and adhesion of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Embodiment 1:
[0025] A high temperature resistant UV high gloss board, prepare the MDF substrate according to the following material ratio:
[0026] Wood fiber mixture: 1000kg
[0027] Synthetic resin: 120kg
[0028] Moisture-proof solvent: 150kg of 15% paraffin emulsion, 30kg of 3% silane coupling agent, and 50kg of 5% polyvinyl alcohol.
[0029] The wood fiber mixture is mixed with a synthetic resin solution. During the process, a moisture-proof solvent solution is added to make the resin evenly adhere to the fiber surface. The mixed fibers are evenly laid in a molding mold. The mixed fibers form a fiber layer of a certain thickness in the mold. The fiber layer is preliminarily compacted by a pre-pressing machine to give it a preliminary shape and density. The pre-pressed fiber layer is sent to a hot press and hot-pressed under high temperature and high pressure conditions. During the hot pressing process, the resin will melt and solidify, so that the fibers are tightly combined together to form a board with a certain density and strength. The hot-pressed board needs to be gradually cooled in a cooling device to prevent deformation of the board. The formed board is cut to the required size and the surface of the board is sanded to make it smooth.
[0030] Comparative Example 1:
[0031] Prepare the MDF substrate according to the following material ratio:
[0032] Wood fiber mixture: 1000kg
[0033] Synthetic resin: 120kg
[0034] Moisture-proof solvent: 150kg of 15% paraffin emulsion.
[0035] The MDF substrate was prepared in the same manner as in Example 1.
[0036] Comparative Example 2:
[0037] Prepare the MDF substrate according to the following material ratio:
[0038] Wood fiber mixture: 1000kg
[0039] Synthetic resin: 120kg
[0040] Moisture-proof solvent: 30kg of 3% silane coupling agent.
[0041] The MDF substrate was prepared in the same manner as in Example 1.
[0042] Comparative Example 3:
[0043] Prepare the MDF substrate according to the following material ratio:
[0044] Wood fiber mixture: 1000kg
[0045] Synthetic resin: 120kg
[0046] Moisture-proof solvent: 5% polyvinyl alcohol 50kg.
[0047] The MDF substrate was prepared in the same manner as in Example 1.
[0048] The MDF substrates prepared in the above-mentioned Example 1 and Comparative Examples 1 to 3 were tested for performance, and the following data were obtained:
[0049] Water absorption Dimensional change rate tensile strength Surface roughness Surface gloss Embodiment 1 6% 0.5% 32 MPa 1μm 84GU Comparative Example 1 11% 1.2% 27MPa 2μm 72GU Comparative Example 2 13% 1.8% 26MPa 2μm 75GU Comparative Example 3 12% 1.5% 27MPa 2μm 74GU
[0050] For the water absorption test, soak the sample in water for 24 hours, take out the sample, wipe off the surface moisture with a dry cloth, weigh it, and calculate the water absorption.
[0051] The dimensional change rate is to measure the changes in length and width of the sample before and after immersion, the surface roughness is measured using a surface roughness meter, and the surface gloss is measured using a gloss meter.
[0052] It can be concluded from the above table that the water absorption rate of the MDF substrate prepared by using the paraffin emulsion, silane coupling agent and polyvinyl alcohol together in Example 1 is lower than that of the MDF substrate using only one material in the comparative example, indicating that the MDF substrate prepared in Example 1 has better moisture resistance. While ensuring the low water absorption rate of the MDF substrate, the dimensional change rate of the MDF substrate is smaller, and the tensile strength, surface roughness and surface gloss are all better.
[0053] Embodiment 2:
[0054] Please refer to Figure 1 A high temperature resistant UV high gloss board is processed on the MDF substrate of embodiment 1 with a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating, wherein the ingredients of each coating are as follows:
[0055] Sealing primer: 700g waterborne polyurethane resin, 50g silane coupling agent, 10g polysiloxane defoamer, 10g acrylate leveling agent, 230g deionized water;
[0056] Modified epoxy resin primer: 650g epoxy resin, 250g aromatic amine curing agent, 40g alumina, 10g 2-hydroxy-2-methylpropiophenone, 10g silane coupling agent, 10g acrylate leveling agent, 20g rubber particles, and 10g acetone.
[0057] Intermediate coating: 700g phenolic resin, 100g nano titanium dioxide, 100g organic silicon compound, 50g silane coupling agent, 10g acrylic leveling agent, and 40g acetone.
[0058] Top coating: UV curing resin 700g, 2-hydroxy-2-methylpropiophenone 50g, leveling agent 20g, defoaming agent 10g, diluent: 220g.
[0059] According to the above formula, the sealing primer is prepared and sprayed evenly on the surface of the MDF substrate with a thickness of 10 μm, and dried at 80°C for 30 minutes; then the prepared modified epoxy resin primer is evenly sprayed on the surface of the sealing primer with a thickness of 20 μm, and irradiated under a UV lamp for 60 seconds to ensure complete curing; the intermediate coating is evenly sprayed on the surface of the modified epoxy resin primer with a thickness of 30 μm, and dried: dried at 80°C for 50 minutes; finally, the top coating is sprayed evenly on the surface of the intermediate coating with a thickness of 15 μm, and irradiated under a UV lamp for 50 seconds to ensure complete curing.
[0060] Comparative Example 4:
[0061] On the MDF substrate of Comparative Example 2, a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating are processed, wherein the ingredients of each coating are the same as those of Example 2, and the processing is carried out using the method of Example 2.
[0062] Comparative Example 5:
[0063] On the MDF substrate of Example 1, a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating are processed, wherein the ingredients of each coating are as follows:
[0064] Sealing primer: 700g waterborne polyurethane resin, 50g silane coupling agent, 10g polysiloxane defoamer, 10g acrylate leveling agent, 230g deionized water;
[0065] Modified epoxy resin primer: 650g epoxy resin, 250g aromatic amine curing agent, 10g 2-hydroxy-2-methylpropiophenone, 10g silane coupling agent, 10g acrylate leveling agent, 20g rubber particles, and 50g acetone.
[0066] Intermediate coating: 700g phenolic resin, 100g nano titanium dioxide, 100g organic silicon compound, 50g silane coupling agent, 10g acrylic leveling agent, and 40g acetone.
[0067] Top coating: UV curing resin 700g, 2-hydroxy-2-methylpropiophenone 50g, leveling agent 20g, defoaming agent 10g, diluent: 220g.
[0068] In this comparative example, no aluminum oxide was added to the modified epoxy resin primer layer.
[0069] Comparative Example 6:
[0070] On the MDF substrate of Example 1, a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating are processed, wherein the ingredients of each coating are as follows:
[0071] Sealing primer: 700g waterborne polyurethane resin, 50g silane coupling agent, 10g polysiloxane defoamer, 10g acrylate leveling agent, 230g deionized water;
[0072] Modified epoxy resin primer: 650g epoxy resin, 250g aromatic amine curing agent, 40g alumina, 10g 2-hydroxy-2-methylpropiophenone, 10g silane coupling agent, 10g acrylate leveling agent, 20g rubber particles, and 10g acetone.
[0073] Intermediate coating: 700g phenolic resin, 200g organosilicon compound, 50g silane coupling agent, 10g acrylic leveling agent, and 40g acetone.
[0074] Top coating: UV curing resin 700g, 2-hydroxy-2-methylpropiophenone 50g, leveling agent 20g, defoaming agent 10g, diluent: 220g.
[0075] In this comparative example, nano titanium dioxide is not added to the intermediate coating, but the content of the organic silicon compound is increased.
[0076] The high temperature resistant UV high gloss boards prepared in the above-mentioned Example 2 and Comparative Examples 4 to 6 were subjected to performance testing to obtain the following data:
[0077]
[0078]
[0079] The heat deformation temperature test is to place the sample in a heating medium, gradually increase the temperature, use a heat deformation temperature tester, and record the temperature at which the sample deforms under a specified load.
[0080] The thermal expansion coefficient test is to fix the sample on the instrument, gradually increase the temperature, and use the thermal expansion meter to record the linear expansion or contraction of the sample at different temperatures.
[0081] Thermal shock resistance refers to repeatedly switching the sample between 200°C and -20°C for 10 times and observing the changes in the sample's appearance and performance.
[0082] Use a surface roughness meter and a gloss meter to test the surface smoothness and glossiness of the material under high temperature environment, and the high temperature is 100℃.
[0083] From the above test results, it can be concluded that the high temperature resistant UV high gloss board prepared in Example 2 is significantly better than that in Comparative Example 4 in terms of high temperature resistance, indicating that improving the moisture resistance of the MDF substrate can effectively improve the high temperature resistance of the high temperature resistant UV high gloss board. At the same time, the lack of aluminum oxide in the modified epoxy resin base coating of Comparative Example 5 and the lack of nano-titanium dioxide in the intermediate coating of Comparative Example 6 cannot achieve the high temperature resistance effect of Example 2. Although the amount of organic silicon compounds is increased in Comparative Example 6, the high temperature resistance effect is not as good as the synergistic effect of nano-titanium dioxide and organic silicon compounds in Example 2.
[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0085] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A high temperature resistant UV high gloss board, comprising an MDF substrate, characterized in that: The MDF substrate contains a moisture-proof solvent, and the surface of the MDF substrate is coated with a sealing primer, a modified epoxy resin base coating, an intermediate coating and a top coating in sequence, wherein the intermediate coating contains nano titanium dioxide, an organic silicon compound and a silane coupling agent.
2. The high temperature resistant UV high gloss board according to claim 1, characterized in that: The MDF substrate is made of the following materials: a wood fiber mixture, a synthetic resin and a moisture-proof solvent, wherein the moisture-proof solvent comprises paraffin emulsion, a silane coupling agent and polyvinyl alcohol, and the paraffin emulsion, the silane coupling agent and the polyvinyl alcohol are mixed in a ratio of 15:3:
5.
3. The high temperature resistant UV high gloss board according to claim 2, characterized in that: The concentration of the paraffin emulsion is 10%-20%, the concentration of the silane coupling agent is 2%-5%, and the concentration of the polyvinyl alcohol is 3%-7%.
4. The high temperature resistant UV high gloss board according to claim 2, characterized in that: The preparation method of the synthetic resin is as follows: dissolving a urea-formaldehyde resin with low formaldehyde release in an appropriate amount of water to prepare a resin solution, adding urea to the resin solution, and stirring evenly to prepare a mixed resin.
5. The high temperature resistant UV high gloss board according to claim 4, characterized in that: The preparation method of the wood fiber mixture is as follows: selecting wood fibers of uniform size and length, removing impurities and dust from the wood fibers, adding active carbon and bamboo charcoal to the cleaned wood fibers, wherein the amount of active carbon and bamboo charcoal added is 0%-2% of the weight of the wood fibers, and obtaining the wood fiber mixture.
6. The high temperature resistant UV high gloss board according to claim 1, characterized in that: The materials of the sealing primer are proportioned as follows by mass: 65%-75% of waterborne polyurethane resin, 3%-6% of silane coupling agent, 0.5%-1% of polysiloxane defoamer, 0.5%-1% of acrylate leveling agent, and the balance of deionized water. The spraying thickness of the sealing primer is 10-20 μm.
7. The high temperature resistant UV high gloss board according to claim 1, characterized in that: The materials of the modified epoxy resin base coating are proportioned as follows by mass: 65%-70% epoxy resin, 25%-30% aromatic amine curing agent, 2%-5% aluminum oxide, 1%-2% 2-hydroxy-2-methylpropiophenone, 1%-2% silane coupling agent, 0.5%-1% acrylate leveling agent, 1%-2% rubber particles, and acetone: balance.
8. The high temperature resistant UV high gloss board according to claim 1, characterized in that: The materials of the intermediate coating are proportioned by mass as follows: 65%-70% phenolic resin, 8%-12% nano titanium dioxide, 8%-12% organic silicon compound, 3%-6% silane coupling agent, 0.5%-1% acrylic leveling agent, and the balance of acetone.
9. The high temperature resistant UV high gloss board according to claim 1, characterized in that: The materials of the top coating are proportioned by mass as follows: 80% UV curing resin, 5% 2-hydroxy-2-methylpropiophenone, 1%-2% leveling agent, 0.5%-1% defoaming agent, and the balance of diluent.
10. A process for preparing a high temperature resistant UV high gloss board, used for preparing the high temperature resistant UV high gloss board according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: The wood fiber mixture is mixed with the synthetic resin solution. During the process, a moisture-proof solvent solution is added to make the resin evenly adhere to the fiber surface. The mixed fibers are evenly laid in a molding mold and hot-pressed. After cutting, the MDF substrate is made; Step 2: Use a spray gun to evenly spray the prepared sealing primer on the surface of the MDF substrate, control the spraying thickness to 10-20μm, put the substrate sprayed with the sealing primer into a drying room, control the temperature at 60-80℃, and dry it for 30-60 minutes to ensure that the primer is completely dry; Step 3: spray the prepared modified epoxy resin primer evenly on the surface of the closed primer, control the spraying thickness to 10-20 μm, put the substrate sprayed with the primer into the UV curing equipment, turn on the UV lamp, and irradiate for 30-60 seconds to form a uniform modified epoxy resin primer; Step 4: Spray the prepared intermediate coating evenly on the surface of the modified epoxy resin base coating with a spraying thickness of 20-30 μm, put the substrate sprayed with the intermediate coating into a drying room, control the temperature at 60-80°C, and dry for 30-60 minutes; Step 5: Spray the prepared topcoat liquid evenly on the surface of the intermediate coating with a spraying thickness of 10-20 μm. Place the substrate sprayed with the topcoat liquid into the UV curing equipment, turn on the UV lamp, and irradiate for 30-60 seconds to form a uniform high-gloss coating.
Citation Information
Cited By
High-strength PP base film and preparation method thereof
CN120842656A